Response of a turbulent boundary layer to rapid freestream acceleration - Saavedra, J.; Poggie, J.; Paniagua, G. (Physics of fluids (1994), 2020)
In a wide range of fluid machinery, a turbulent boundary layer can be exposed to rapid transients of the freestream conditions. A simplified model of the boundary layer response would provide valuable guidance in understanding these situations in multiple engineering applications. To this end, a turbulent boundary flow, subject to freestream acceleration, was explored through high-fidelity simulations and Reynolds-averaged Navier–Stokes calculations. Test cases were considered in which the flow over a flat plate accelerated from Mach 0.3 up to 0.6 over two time scales, 10 ms and 25 ms. Based on data from the calculations, the integral boundary layer momentum equation was simplified to propose a new reduced-order model capable of computing the evolution of the boundary layer under external flow transients. Given the initial boundary layer height, and the temporal evolution of the freestream pressure, velocity, and density, the model predicts the transient development of the boundary layer. With the transient boundary layer profile known, the temporal history of the skin friction and heat transfer can be predicted, taking advantage of standard shear stress correlations and the Reynolds analogy.